Practical English language teaching : - Bailey, Kathleen M. (McGraw-Hill ESL/ELT, 2005)
"The Practical English Language Teaching" series offers a thorough yet practical overview of language teaching strategies and methodology for teachers and teachers in preparation. Each title in the series is designed as a special-interest core text for teacher training courses. These titles offer tips and techniques on the teaching of listening, speaking, grammar and the role of assessment in language learning. Each contributor addresses key teaching challenges in his/her area of expertise. Each user-friendly book is divided into three sections: exploring skills, exploring language and supporting the learning process. The principles outlined in each chapter are richly illustrated with vignettes and situations from real classrooms. In this way, the reader can see how the principles are put into practice in the classroom.